Integrating in situ formation of nanozymes with three-dimensional dendritic mesoporous silica nanospheres for hypoxia-overcoming photodynamic therapy. Issue 48 (30th November 2018) - Cai, Xiaoli; Luo, Yanan; Song, Yang; Liu, Dong; Yan, Hongye; Li, He; Du, Dan; Zhu, Chengzhou; Lin, Yuehe
Abstract : A mitochondria-targeting and O2 -evolving PDT nanoplatform based on 3D-dendritic MSNs was proposed for highly efficient cancer PDT treatment. Abstract : Despite great progress in photodynamic therapy (PDT), the therapeutic effect is still limited by some points, such as tumor hypoxia, the short lifetime and the limited action region of 1 O2 . Herein, a special kind of three-dimensional dendritic mesoporous silica nanosphere (3D-dendritic MSN) was synthesized and used as a robust nanocarrier to deliver abundant hydrophobic photosensitizer chlorin e6 (Ce6) to the A549 lung cancer cells. To address the tumor hypoxia issue, the nanozyme Pt nanoparticles (Pt NPs) were immobilized onto the channels of 3D-dendritic MSNs to catalyze the conversion of intracellular H2 O2 to oxygen. Moreover, due to the in situ reduction process, the uniform Pt NPs distributed well on the surface of 3D-dendritic MSNs with high homogeneous dispersity. Additionally, a mitochondria-targeting ligand, triphenylphosphine (TPP), was conjugated to the Pt-decorated 3D-dendritic MSN composites to form a mitochondria targeted system for the PDT. In a combination of the peroxidase-like Pt NPs with mitochondria-targeting ability of TPP, a reactive oxygen species (ROS) burst in the mitochondria was achieved and resulted in the cell apoptosis. This well-designed system shows an enhanced PDT effect of killing A549 cells, and promotes a new H2 O2 -activatable strategy to overcome hypoxia for tumor PDT.